Neonatal Intestinal Obstruction: When to Suspect Duplication Cyst of Bowel as the Cause - Rizwan Ahmad Khan; Shagufta Wahab; Imran Ghani (EL-Med-Pub, 2020)
Background: Duplication cyst is a rare cause of neonatal intestinal obstruction. Their most common location is the small intestine. The clinical presentation is extremely variable depending upon its size, location and type and the age of the patient and are mainly encountered during infancy or early childhood. The diagnosis is very difficult in neonates. This study was undertaken to study their presentation, diagnostic modality of choice and further management in neonatal age group. Materials and Methods: This was a retrospective study performed at the Department of Paediatric Surgery, J .N Medical College Hospital, AMU Aligarh from July 2008 to June 2014. The data was analyzed with respect to demographic profile of the neonates, their initial clinical presentation, radiological features and subsequent event leading to intervention, operative features and outcome. Results: There were a total of seven neonates between ages of 3 days and 21 days who were diagnosed as cases of intestinal obstruction due to duplication cyst. The majority of the patients were having ileal duplication cyst (n=4). Ultrasonography played important role in majority of the cases for diagnosis. There was one patient in which the diagnosis was confused with ileal atresia. All the patients underwent excision with restoration of bowel continuity. Conclusion: The diagnosis of intestinal obstruction in neonate due to duplication cyst is difficult. It has varied presentation and preoperative diagnosis at times may be challenging. Surgery is the mainstay of the treatment.